Study Proportions and Chemical Composition of red and white muscles of Tilapia Zillii and Acanthopagrus latus - Oda, Yasir W. (Iraqi Journal of Aquaculture, 2021)
The present study deals with two types of teleost; Tilapia zillii (Cichlidae), and Acanthopagrus latus (Sparidae), to study some aspects with relation to the fish activity such as the proportion of red and white muscle fibers, and estimation of the chemical content (protein, lipid, moisture, ash) in different regions of fish studied. The results showed that the red muscles less than the white muscles in (R1, R2) in studied fish, The red muscles ranged between (5.01–10.5%) and (4.67–9.64%) in T. zillii and A. latus respectively, while the proportion of white muscles were ranged between (94.98–88.49%) and (95.32–90.35%) in T. zillii and A. latus respectively beside to increasing of red muscles towards of the posterior region (caudal peduncle), therefore these fish are put in the intermediate activity. The results which related to chemical content in muscles including (protein, lipid, moisture, ash) in (R1, R2) from fish body, showed that the proportion of protein were ranged (17.97–19.05%) and (16.89–17.46%) in T. zillii and A. latus respectively, while the proportion of lipid were ranged between (1.54–2.08%) and (3.08–3.13%) in fish studied, therefore T. zillii put in non-lipid fishes or flesh fishes, while A. latus put in intermediate lipid fishes.